1981
DOI: 10.1017/s0263593300009949
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of an early Proterozoic strata-bound Cu-Co-Zn deposit, Outokumpu, Finland

Abstract: The massive pyrite-pyrrhotite-chalcopyrite-sphalerite deposit of Outokumpu, comprising the Keretti and Vuonos orebodies, is a deformed and metamorphosed strata-bound mass associated with mineralised stockworks. Mobilisation of much of the ore followed formation of large recumbent isoclinal folds that are the major structures of the surrounding rocks and associated with the modification of originally flat saucer-shaped ore lenses into elongate ruler-shaped masses. Further modification of shape took place at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
132
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 46 publications
10
132
0
Order By: Relevance
“…1) form part of the Kalevian schists in the nomenclature of Nykänen (1975) and, on the basis of regional structural relationships, can be subdivided into two nappe units, the Outokumpu and the Savonranta nappes, the latter being uppermost (Koistinen 1981;Halden 1982 b;Park and Bowes 1983, fig. 18).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…1) form part of the Kalevian schists in the nomenclature of Nykänen (1975) and, on the basis of regional structural relationships, can be subdivided into two nappe units, the Outokumpu and the Savonranta nappes, the latter being uppermost (Koistinen 1981;Halden 1982 b;Park and Bowes 1983, fig. 18).…”
Section: Geological Settingmentioning
confidence: 99%
“…2). Also shown is the distribution of aluminosilicate polymorphs, garnet and cordierite (the latter indicates the position of the layered schist); data from Nykä-nen (1975) and Koistinen (1981) included; comp. foln.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the composition of the parental magma was basaltic with a MgO content of about 12 wt.% (Peltonen, 1995a(Peltonen, , 2005. Emplacement of magma was accompanied the gently dipping D 2 folding and thrusting event (Mäkinen & Makkonen, 2004;Makkonen, 2005), which was a response to convergence and thrusting of Svecofennian terranes over the Archaean cratonic foreland (Koistinen, 1981). During D 3 the subhorizontal D 1-2 structures were reoriented into steeper orientations (Mäkinen & Makkonen, 2004).…”
Section: Introductionmentioning
confidence: 99%